Bright Soliton Solutions for Time Fractional Korteweg-de Vries Equation - Ozkan, Erdogan Mehmet; Ozkan, Ayten (AMER INST PHYSICS, 2021)
In this work, He's semi-inverse variation method and the ansatz method with the modified Riemann-Liouville derivative are used to construct the exact solutions for time fractional Korteweg-de Vries (KdV) equation. The fractional KdV equation is transformed to another non-linear differential equation by travelling wave transformations and then these two methods are applied to find the solution.
Keywords: GORDON EQUATIONS; KDV; TRANSFORM; EVOLUTION; SYSTEM; Operations Research & Management Science; Mathematics